Selection and control of human factors in civil construction companies - García Zapata, Teonila Doria (2012)
Although the construction has very singular landlords, the personnel administration necessarily does not follow the methods most suitable of selection and control of workers/workers. This industry must have specialists in diverse fields of the construction such as in: bridges, highways, ports, railroads, etc. The greater contribution of the present investigation is based on the proposal of selection and control of workers on the basis of the management by competitions, since the construction in Peru is based on the empirical knowledge of its daily task. It is so a structure of the profile of the worker according to the area sets out in which it must work, the description of the position, mental, physical abilities, educational level and general knowledge that must have to improve the efficiency and yield in the execution of a civil construction site.